Using Delphi method to develop Chinese women's cervical cancer screening intention scale based on planned behavior theory - Tingting Xin; Xian Ding; Han Gao; Chunting Li; Yuting Jiang; Xiao Chen (BMC, 2022)
Abstract Background Cervical cancer is the most common malignant tumor in women with a high mortality rate. However, the awareness and participation of women in cervical cancer screening were not high, and rare attention was paid to cervical cancer screening. The extensive promotion and execution of cervical cancer screening in China are still facing difficulties. In order to fully comprehend and evaluate the barriers and promote factors of cervical cancer screening in women, the objective of this study was to develop a scientifically sound and clinically useful Chinese cervical cancer screening intention scale. This study would allow for the development of targeted interventions which may contribute to the increase of individual participation in cervical cancer screening going forward. Methods This study used the Delphi method to construct a Chinese cervical cancer screening intention scale based on the theory of planned behavior (TPB) and evaluate its validity. The study was based on the overview of the TPB questionnaire proposed by Ajzen, and was conducted through the literature search and two rounds of the Delphi expert consultation. According to the literature search published from 2012 to 2022, the scale item pool was established and a questionnaire was designed. A survey of 16 experts from 6 different provinces, cities and regions in China was conducted, and the Delphi technique was used to collect and analyze expert opinions data. Results The final scale consisted of 4 dimensions and 23 items. The response rates in two rounds of expert consultation were 80% and 93.75%, respectively, with authority coefficients of 0.928 and 0.930. Variation coefficients varied from 0.07 to 0.21. Dimensions included "attitude towards behavior", "subjective norm", "perceived behavioral control" and "behavioral intention". Conclusions Women's cervical cancer screening intentions could be assessed with the scale, since it had high validity and reliability, as well as high authority and coordination, meanwhile affording explanations and improving the efficiency of interventions.